Composition for manufacturing porous membrane, method for manufacturing porous membrane, and porous membrane
By using a porous membrane manufacturing method that combines specific resin components and solvents, the problem of flow reduction caused by small pore sizes in the prior art is solved, and a porous membrane with small pore size and high flow rate is realized, which is suitable for semiconductor manufacturing and other fields.
Patent Information
- Application Number
- CN202411068974.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-04
- Filing Date
- 2024-08-06
- Publication Date
- 2025-03-04
AI Technical Summary
When the pore size is reduced to capture small foreign matter, the permeability and flow rate are reduced, making it difficult to achieve small pore size and flow rate improvement at the same time.
A composite film manufacturing composition is used which includes a resin component selected from the group consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide and polyethersulfone and a specific solvent. The organic solvent with a boiling point below 200°C and a nitrogen-containing polar solvent with a boiling point above 200°C as solvent is used as solvents to form a composite film and undergo a heating and particle removal process to increase the flow rate of the porous film.
It is achieved to increase the flow rate of the porous membrane while maintaining a small pore size, enhance the strength of the membrane, inhibit pore collapse, and improve the efficiency of filtration or ventilation.
Smart Images

Figure BDA0004980249410000091 
Figure BDA0004980249410000092 
Figure BDA0004980249410000271
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for producing a porous film, a method for producing a porous film, and a porous film. Background Art
[0002] Various porous membranes have been used in filters and the like as gas or liquid separation membranes. In recent years, porous membranes have also been used as separators for secondary batteries such as lithium batteries.
[0003] For example, as a method for producing a porous polyimide film, the following method is known: a varnish obtained by dispersing silica particles in a solution of polyamic acid or polyimide is applied to a substrate, and then the coated film is heated as needed to obtain a polyimide film containing silica particles, and then the silica in the polyimide film is dissolved and removed using an aqueous hydrogen fluoride solution to make the polyimide film porous (see Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 5605566 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The above-mentioned porous membrane is required to have a small pore diameter.
[0009] For example, in the manufacture of semiconductors, porous membranes are used as filters for removing foreign matter contained in washing liquids, coating liquids, etc. With the development of semiconductor miniaturization, the size of foreign matter, which is the main factor of defects, has also become smaller. In order to capture small foreign matter, a porous membrane with a small pore size is required. It should be noted that a porous membrane with a small pore size can be manufactured by using a porous membrane manufacturing composition (varnish) containing microparticles such as silicon dioxide with a small particle size.
[0010] However, when the pore diameter of the porous membrane is reduced, the permeability (liquid permeability, air permeability) of the porous membrane is reduced, and the flow rate of the liquid and gas passing through the porous membrane is reduced.
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a composition for producing a porous membrane, a method for producing a porous membrane, and a porous membrane capable of improving the flow rate of the produced porous membrane.
[0012] Means for solving problems
[0013] The inventors of the present application have repeatedly conducted in-depth research to solve the above-mentioned problems. As a result, it was found that by using an organic solvent having a boiling point of less than 200°C at atmospheric pressure and a nitrogen-containing polar solvent having a boiling point of more than 200°C at atmospheric pressure as a solvent (S) in a composition for producing a porous membrane comprising at least one resin component (A) selected from the group consisting of polyamic acid, polyimide, polyamide-imide precursor, polyamide-imide and polyethersulfone, microparticles (B) and a solvent (S), the above-mentioned problems can be solved, thereby completing the present invention. Specifically, the present invention provides the following aspects.
[0014] [1] A composition for producing a porous film, comprising a resin component (A), fine particles (B) and a solvent (S), wherein the resin component (A) is at least one selected from the group consisting of polyamic acid, polyimide, a polyamideimide precursor, polyamideimide and polyethersulfone;
[0015] The aforementioned solvent (S) includes an organic solvent (S1) and an organic solvent (S2),
[0016] The organic solvent (S1) is an organic solvent having a boiling point of less than 200° C. under atmospheric pressure,
[0017] The organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure.
[0018] [2] The composition for producing a porous membrane as described in [1] above, wherein the nitrogen-containing polar solvent as the organic solvent (S2) is at least one selected from the group consisting of nitrogen-containing heterocyclic compounds that may have a substituent and aromatic hydrocarbons substituted with a nitrogen-containing group.
[0019] [3] The composition for producing a porous membrane according to [2] above, wherein the organic solvent (S2) is at least one selected from the group consisting of 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, N-ethyl-2-pyrrolidone and nitrobenzene.
[0020] [4] The composition for producing a porous film according to any one of [1] to [3] above, wherein the organic solvent (S1) is an aliphatic amide solvent.
[0021] [5] The composition for producing a porous film according to any one of [1] to [4] above, wherein the organic solvent (S1) is dimethylacetamide.
[0022] [6] The composition for producing a porous membrane as described in any one of [1] to [5] above, wherein the ratio of the mass of the organic solvent (S2) to the mass of the solvent (S) is 5 mass % to 70 mass %.
[0023] [7] The composition for producing a porous membrane as described in any one of [1] to [6] above, wherein the content of the organic solvent (S2) is 100 parts by mass or more and 900 parts by mass or less relative to 100 parts by mass of the resin component (A).
[0024] [8] A method for producing a porous membrane, comprising the following steps:
[0025] a composite film forming step of forming a composite film formed from the porous film-producing composition described in any one of [1] to [7] above on a substrate;
[0026] a heating step of heating the composite film to remove a portion of the solvent (S) from the composite film; and
[0027] The fine particle removal step is to remove the fine particles (B) from the composite film after the heating step.
[0028] [9] The method for producing a porous film according to [8] above, wherein the resin component (A) comprises at least one of a polyamic acid and a polyamideimide precursor,
[0029] The production method includes a firing step of firing the composite film during the heating step or after the heating step and before the fine particle removal step.
[0030]
[10] A porous membrane comprising at least one resin component selected from the group consisting of polyimide, polyamideimide and polyethersulfone and a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure,
[0031] The porous membrane is manufactured using a manufacturing method comprising the following steps: a step of forming a composite membrane formed from the porous membrane manufacturing composition described in any one of [1] to [7] on a substrate; a step of heating the composite membrane to remove a portion of the solvent (S) from the composite membrane; and a step of removing the microparticles (B) from the heated composite membrane.
[0032] Effects of the Invention
[0033] According to the present invention, a composition for producing a porous membrane, a method for producing a porous membrane, and a porous membrane capable of improving the flow rate of the produced porous membrane can be provided. DETAILED DESCRIPTION
[0034] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments at all and can be implemented with appropriate modifications within the scope of the purpose of the present invention.
[0035] "Composition for producing porous membrane"
[0036] The composition for producing a porous film (hereinafter, also described as "varnish") comprises a resin component (A), microparticles (B) and a solvent (S), wherein the resin component (A) is at least one selected from the group consisting of polyamic acid, polyimide, polyamideimide precursor, polyamideimide and polyethersulfone. The solvent (S) comprises an organic solvent (S1) and an organic solvent (S2). The organic solvent (S1) is an organic solvent having a boiling point of less than 200°C at atmospheric pressure. The organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of more than 200°C at atmospheric pressure.
[0037] [Resin component (A)]
[0038] As described above, the composition for producing a porous film contains at least one resin component (A) selected from the group consisting of polyamic acid, polyimide, a polyamideimide precursor, polyamideimide, and polyethersulfone. These resin components (A) are described below.
[0039] [Polyamic acid]
[0040] As the polyamic acid, any product obtained by polymerizing tetracarboxylic dianhydride and diamine can be used without particular limitation. The amount of tetracarboxylic dianhydride and diamine used is not particularly limited, but it is preferred to use 0.50 to 1.50 mol of diamine, more preferably 0.60 to 1.30 mol of diamine, and particularly preferably 0.70 to 1.20 mol of diamine relative to 1 mol of tetracarboxylic dianhydride.
[0041] Tetracarboxylic dianhydride can be suitably selected from tetracarboxylic dianhydride which has been used as the synthetic raw material of polyamic acid.Tetracarboxylic dianhydride can be aromatic tetracarboxylic dianhydride or aliphatic tetracarboxylic dianhydride. From the aspect of the heat resistance of the obtained polyimide resin, aromatic tetracarboxylic dianhydride is preferably used.Tetracarboxylic dianhydride can be used alone or in combination of two or more.
[0042] Preferred specific examples of the aromatic tetracarboxylic dianhydride include pyromellitic dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2,6,6-biphenyltetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, and 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride. 、3,3',4,4'-benzophenonetetracarboxylic dianhydride、bis(3,4-dicarboxyphenyl)ether dianhydride、bis(2,3-dicarboxyphenyl)ether dianhydride、2,2',3,3'-benzophenonetetracarboxylic dianhydride、4,4-(p-phenylenedioxy)diphthalic dianhydride、4,4-(isophenylenedioxy)diphthalic dianhydride、1,2,5,6-naphthalenetetracarboxylic dianhydride、1,4,5,8-naphthalenetetracarboxylic dianhydride、2,3,6,7-naphthalenetetracarboxylic dianhydride、1,2,3,4-pyromellitic dianhydride、3,4,9,10-perylenetetracarboxylic dianhydride、2,3,6,7-anthracenetetracarboxylic dianhydride、1,2,7,8-phenanthrenetetracarboxylic dianhydride、9,9-bis(phthalic anhydride)fluorene anhydride)fluorene), 3,3',4,4'-diphenyl sulfone tetracarboxylic acid dianhydride, etc. As aliphatic tetracarboxylic acid dianhydride, for example, ethylene tetracarboxylic acid dianhydride, butane tetracarboxylic acid dianhydride, cyclopentane tetracarboxylic acid dianhydride, cyclohexane tetracarboxylic acid dianhydride, 1,2,4,5-cyclohexane tetracarboxylic acid dianhydride, 1,2,3,4-cyclohexane tetracarboxylic acid dianhydride, etc. Among them, from the perspective of price, ease of acquisition, etc., 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride and pyromellitic acid dianhydride are preferred. In addition, these tetracarboxylic acid dianhydrides can be used alone or in combination of two or more.
[0043] The diamine can be suitably selected from the diamines that have been used as the synthetic raw materials of polyamic acid. The diamine can be an aromatic diamine or an aliphatic diamine. From the aspect of the heat resistance of the obtained polyimide resin, an aromatic diamine is preferably used. These diamines can be used alone or in combination of two or more.
[0044] Examples of the aromatic diamine include diamino compounds to which 1 or 2 to 10 phenyl groups are bonded, specifically phenylenediamine and its derivatives, diaminobiphenyl compounds and their derivatives, diaminodiphenyl compounds and their derivatives, diaminotriphenyl compounds and their derivatives, diaminonaphthalene and its derivatives, aminophenylaminoindanes and their derivatives, diaminotetraphenyl compounds and their derivatives, diaminohexaphenyl compounds and their derivatives, and Cardo-type fluorenediamine derivatives.
[0045] Phenylenediamine includes m-phenylenediamine, p-phenylenediamine and the like. Phenylenediamine derivatives include diamines to which an alkyl group such as a methyl group or an ethyl group is bonded, for example, 2,4-diaminotoluene, 2,4-triphenylenediamine and the like.
[0046] In the diaminobiphenyl compound, two aminophenyl groups are bonded to each other, such as 4,4'-diaminobiphenyl and 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl.
[0047] The diaminodiphenyl compound is a compound in which two aminophenyl groups are bonded to each other via other groups as phenyl groups. The bond is an ether bond, a sulfonyl bond, a thioether bond, a bond formed by an alkylene group or a derivative thereof, an imino bond, an azo bond, a phosphine oxide bond, an amide bond, a ureylene bond, etc. The number of carbon atoms in the alkylene bond is about 1 to 6. The derivative group of the alkylene group is an alkylene group substituted with one or more halogen atoms or the like.
[0048] Examples of the diaminodiphenyl compound include 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl ketone, 3,4'-diaminodiphenyl ketone, 2,2-bis(p-aminophenyl)propane, 2,2'-bis(p-aminophenyl)hexafluoropropane, 4-methyl-2,4-bis(p-aminophenyl)-1-pentene, 4-methyl-2,4-bis(p-aminophenyl)-1-pentene, and 4-methyl-2,4-bis(p-aminophenyl)-1-pentene. Bis(p-aminophenyl)-2-pentene, iminodiphenylamine, 4-methyl-2,4-bis(p-aminophenyl)pentane, bis(p-aminophenyl)phosphine oxide, 4,4'-diaminoazobenzene, 4,4'-diaminodiphenyl urea, 4,4'-diaminodiphenylamide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, etc.
[0049] Among them, p-phenylenediamine, m-phenylenediamine, 2,4-diaminotoluene, and 4,4′-diaminodiphenyl ether are preferred in view of price, availability, and the like.
[0050] The diaminotriphenyl compound is a compound in which two aminophenyl groups and one phenylene group are bonded via other groups. The other groups can be selected from the same groups as the diaminodiphenyl compound. Examples of the diaminotriphenyl compound include 1,3-bis(m-aminophenoxy)benzene, 1,3-bis(p-aminophenoxy)benzene, and 1,4-bis(p-aminophenoxy)benzene.
[0051] Examples of diaminonaphthalene include 1,5-diaminonaphthalene and 2,6-diaminonaphthalene.
[0052] Examples of aminophenylaminoindan include 5- or 6-amino-1-(p-aminophenyl)-1,3,3-trimethylindan.
[0053] Examples of the diaminotetraphenyl compound include 4,4'-bis(p-aminophenoxy)biphenyl, 2,2'-bis[p-(p'-aminophenoxy)phenyl]propane, 2,2'-bis[p-(p'-aminophenoxy)biphenyl]propane, and 2,2'-bis[p-(m-aminophenoxy)phenyl]benzophenone.
[0054] Examples of the Cardo-type fluorene diamine derivative include 9,9-dianiline fluorene and the like.
[0055] The carbon number of the aliphatic diamine may be, for example, about 2 to 15. Specific examples of the aliphatic diamine include pentamethylenediamine, hexamethylenediamine, and heptamethylenediamine.
[0056] In addition, the compound in which the hydrogen atom of these diamines is substituted with at least one substituent selected from the group consisting of a halogen atom, a methyl group, a methoxy group, a cyano group, a phenyl group, etc. may be sufficient.
[0057] The method for producing the polyamic acid is not particularly limited, and for example, a known method such as a method of reacting an acid and a diamine component in a solvent can be employed.
[0058] The reaction of tetracarboxylic dianhydride and diamine is usually carried out in a solvent. The solvent used in the reaction of tetracarboxylic dianhydride and diamine is not particularly limited as long as it can dissolve tetracarboxylic dianhydride and diamine and does not react with tetracarboxylic dianhydride and diamine. The solvent can be used alone or in combination of two or more.
[0059] Examples of the solvent used in the reaction of tetracarboxylic dianhydride and diamine include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, N,N-diethylformamide, N-methylcaprolactam, and N,N,N',N'-tetramethylurea; lactone-based polar solvents such as β-propiolactone, γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, and ε-caprolactone; dimethyl sulfoxide; acetonitrile; fatty acid esters such as ethyl lactate and butyl lactate; ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dioxane, tetrahydrofuran, methyl cellosolve acetate, and ethyl cellosolve acetate; and phenolic solvents such as cresols and xylene-based mixed solvents.
[0060] These solvents may be used alone or in combination of two or more. The amount of the solvent used is not particularly limited, but it is desirable that the content of the generated polyamic acid is 5 to 50% by mass.
[0061] As the solvent used in the reaction of tetracarboxylic dianhydride and diamine, the solvent (S) contained in the varnish is preferably used, specifically the organic solvent (S1) and the organic solvent (S2) described in detail later. As the solvent used in the reaction of tetracarboxylic dianhydride and diamine, when the organic solvent (S1) contained in the varnish is used, for example, the varnish containing the organic solvent (S1) and the organic solvent (S2) can be easily manufactured by adding the organic solvent (S2) after the reaction of tetracarboxylic dianhydride and diamine.
[0062] When the organic solvent (S1) or (S2) contained in the varnish is not used as the solvent used in the reaction of tetracarboxylic dianhydride and diamine, the solvent may be replaced with the organic solvent (S1) or (S2) after the reaction.
[0063] The polymerization temperature is usually -10 to 120° C., preferably 5 to 30° C. The polymerization time varies depending on the composition of the raw materials used, but is usually 3 to 24 hours.
[0064] The polyamic acid may be used alone or in combination of two or more.
[0065] [Polyimide]
[0066] The structure and molecular weight of the polyimide are not limited, and known polyimides can be used. The polyimide may have a functional group capable of condensation such as a carboxyl group on the side chain or a functional group that promotes a crosslinking reaction during firing. In addition, a soluble polyimide that can be dissolved in the organic solvent (S1) or the organic solvent (S2) contained in the varnish is preferred.
[0067] In order to prepare a polyimide soluble in an organic solvent (S1) or an organic solvent (S2), it is effective to use a monomer for introducing a soft curved structure into the main chain, for example, the following monomers: aliphatic diamines such as ethylenediamine, hexamethylenediamine, 1,4-diaminocyclohexane, 1,3-diaminocyclohexane, and 4,4'-diaminodicyclohexylmethane; 2-methyl-1,4-phenylenediamine, o-tolidine, m-tolidine, Aromatic diamines such as 3,3'-dimethoxybenzidine and 4,4'-diaminobenzanilide; polyoxyalkylene diamines such as polyoxyethylene diamine, polyoxypropylene diamine, and polyoxybutylene diamine; polysiloxane diamine; 2,3,3',4'-oxydiphthalic anhydride, 3,4,3',4'-oxydiphthalic anhydride, 2,2-bis(4-hydroxyphenyl)propane dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, etc. In addition, the use of monomers having functional groups that improve solubility in solvents, such as 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2-trifluoromethyl-1,4-phenylenediamine, etc., is also effective. In addition, in addition to the monomers used to improve the solubility of the above-mentioned polyimide, the same monomers as those described in the above-mentioned polyamic acid column can also be used in combination within the range that does not inhibit the solubility.
[0068] The polyimide and its monomer may be used alone or in combination of two or more.
[0069] There is no particular restriction on the means for manufacturing polyimide. For example, known methods such as chemical imidization or thermal imidization of polyamic acid can be adopted. As such polyimide, aliphatic polyimide (all aliphatic polyimide), aromatic polyimide, etc. can be cited, preferably aromatic polyimide. As aromatic polyimide, polyimide obtained by ring-closing reaction of polyamic acid with repeating unit shown in formula (1) by heat or chemical means or polyimide with repeating unit shown in formula (2) can be cited. In the formula, Ar represents an aromatic group. These polyimides can then be dissolved in the organic solvent (S1) and the organic solvent (S2) used.
[0070] [Chemical formula 1]
[0071]
[0072] [Chemical formula 2]
[0073]
[0074] [Polyamideimide and polyamideimide precursor]
[0075] The structure and molecular weight of the polyamide-imide are not limited, and known polyamide-imides can be used. The polyamide-imide may have a functional group capable of condensation such as a carboxyl group on the side chain or a functional group that promotes a crosslinking reaction during firing. In addition, a soluble polyamide-imide that can be dissolved in the organic solvent (S1) or the organic solvent (S2) contained in the varnish is preferred.
[0076] Polyamideimide can generally use the following resins without particular limitation: (i) a resin obtained by reacting an acid having a carboxyl group and an anhydride group in one molecule such as trimellitic anhydride with a diisocyanate; (ii) a resin obtained by imidizing a precursor polymer (polyamideimide precursor) obtained by reacting a reactive derivative of the above acid such as chlorinated trimellitic anhydride with a diamine; and the like.
[0077] Examples of the acid or its reactive derivative include trimellitic anhydride, trimellitic anhydride halides such as trimellitic anhydride and trimellitic anhydride chloride, and trimellitic anhydride esters.
[0078] Examples of the optional diamine include the diamines exemplified in the description of the polyamic acid described above. In addition, a diaminopyridine-based compound may also be used.
[0079] The above-mentioned arbitrary diisocyanate is not particularly limited, and examples thereof include diisocyanate compounds corresponding to the above-mentioned arbitrary diamines, and specifically, m-phenylene diisocyanate, p-phenylene diisocyanate, o-tolidine diisocyanate, diisocyanate), p-phenylene diisocyanate, m-phenylene diisocyanate, 4,4'-oxybis(phenyl isocyanate), 4,4'-diisocyanate diphenylmethane, bis[4-(4-isocyanate phenoxy)phenyl]sulfone, 2,2'-bis[4-(4-isocyanate phenoxy)phenyl]propane, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, 3,3'-diethyldiphenyl-4,4'-diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, m-xylene diisocyanate, p-xylene diisocyanate, naphthalene diisocyanate, and the like.
[0080] As the raw material monomer of polyamide-imide, in addition to the above, compounds described in the form of general formula in Japanese Patent Publication No. 63-283705 and Japanese Patent Publication No. 2-198619 can also be used. In addition, the imidization in the method of the above (ii) can be any of thermal imidization and chemical imidization. As chemical imidization, a method in which a composite film (unfired composite film) formed by a varnish containing a polyamide-imide precursor, etc. is immersed in acetic anhydride or a mixed solvent of acetic anhydride and isoquinoline can be adopted. It should be noted that the polyamide-imide precursor can also be said to be a polyimide precursor based on the viewpoint of being a precursor before imidization.
[0081] The polyamideimide contained in the varnish may be (1) a polymer obtained by reacting an acid such as trimellitic anhydride with a diisocyanate, (2) a polymer obtained by imidizing a precursor polymer obtained by reacting a reactive derivative of the above acid such as chlorotrimellitic anhydride with a diamine, etc. In this specification and claims, "polyamideimide precursor" refers to a polymer before imidization (precursor polymer).
[0082] The polyamideimide and the polyamideimide precursor may be used alone or in combination of two or more thereof. In addition, for the polyamideimide, the above-mentioned polymer, raw material monomer and oligomer may be used alone or in combination of two or more thereof.
[0083] [Polyethersulfone]
[0084] The polyethersulfone is not particularly limited as long as it is soluble in the organic solvent (S1) and the organic solvent (S2) used in the varnish. The polyethersulfone can be appropriately selected according to the purpose of the porous membrane to be manufactured, and can be hydrophilic or hydrophobic. In addition, it can be an aliphatic polyethersulfone or an aromatic polyethersulfone. The mass average molecular weight is, for example, 5000 to 1,000,000, preferably 10,000 to 300,000.
[0085] [Microparticles (B)]
[0086] The material of the fine particles (B) is not particularly limited as long as it is insoluble in the solvent (S) contained in the varnish and can be removed from the composite film (resin-fine particle composite film) later, and a known material can be used.
[0087] For example, inorganic materials include metal oxides such as silicon dioxide (silicon dioxide), titanium oxide, and aluminum oxide (Al2O3), and organic materials include organic polymer particles such as high molecular weight olefins (polypropylene, polyethylene, etc.), polystyrene, epoxy resins, cellulose, polyvinyl alcohol, polyvinyl butyral, polyester, and polyether.
[0088] Specifically, as the fine particles (B), for example, colloidal silica can be cited. Among them, when monodisperse spherical silica particles are selected, uniform pores can be formed, which is preferred.
[0089] In addition, the fine particles (B) preferably have a high sphericity and a small particle size distribution index. The fine particles (B) satisfying these conditions have excellent dispersibility in the varnish and can be used in a state where they are not aggregated with each other.
[0090] The average particle size of the fine particles (B) used is, for example, preferably from 10 nm to 500 nm, more preferably from 50 nm to 300 nm, and further preferably from 70 nm to 150 nm.
[0091] In the present specification, the average particle size of the fine particles (B) is referred to as D50, which means a particle size at a cumulative value of 50% in a volume-based particle size distribution determined by a laser diffraction / scattering method.
[0092] It should be noted that the size of the pores derived from the fine particles (B) formed in the porous film is the same as or close to the average particle size of the fine particles (B).
[0093] The fine particles (B) may be used alone or in combination of two or more.
[0094] [Solvent (S)]
[0095] The solvent (S) includes an organic solvent (S1) and an organic solvent (S2). The organic solvent (S1) is an organic solvent having a boiling point (hereinafter simply referred to as "boiling point") under atmospheric pressure of less than 200°C. The organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of 200°C or more under atmospheric pressure.
[0096] By making the varnish contain an organic solvent (S1) having a boiling point below 200°C under atmospheric pressure and an organic solvent (S2) having a nitrogen-containing polar solvent having a boiling point above 200°C under atmospheric pressure as solvent (S), the flow rate of the manufactured porous membrane can be increased as shown in the examples described below.
[0097] This is considered to be due to the following reasons.
[0098] The nitrogen-containing polar solvent interacts with the resin component (A) such as polyamic acid (hydrogen bond, etc.) to improve the orientation of the resin component (A).
[0099] If a nitrogen-containing polar solvent (organic solvent (S2)) having a boiling point of 200°C or more under atmospheric pressure is used in addition to an organic solvent (organic solvent (S1)) having a boiling point of less than 200°C under atmospheric pressure, the nitrogen-containing polar solvent (organic solvent (S2)) remains in the film when heated, and the resin component (A) forms a highly oriented structure, thereby improving the film strength.
[0100] If the film strength is improved, the collapse of the pores can be suppressed. For example, when the resin component (A) contains polyamic acid and a polyamide-imide precursor, when the polyamic acid is changed to polyimide, when the polyamide-imide precursor is changed to polyamide-imide, residual stress is generated due to volume shrinkage, so it is easy to cause collapse of the pores, but if the film strength is high, such collapse of the pores can be suppressed.
[0101] Therefore, the decrease in the flow rate of the fluid (liquid, gas) passing through the porous membrane due to pore collapse can be suppressed, and the flow rate can be improved (increased). In other words, the flow rate of the fluid passing through the porous membrane can be increased.
[0102] For example, when a porous membrane is used as a filter, the processing flow rate (filtration flow rate) can be increased.
[0103] Here, by using a varnish containing fine particles having a small particle size, a porous membrane having a small pore size can be produced.
[0104] On the other hand, if the pore size of the porous membrane is reduced, the permeability (liquid permeability, air permeability) of the porous membrane decreases, and the flow rate of liquid and gas passing through the porous membrane decreases. For example, in the case of filter use, the problem of reduced processing flow rate (filtration flow rate) occurs.
[0105] However, by using the above-mentioned varnish, the flow rate can be increased, so that both the pore size reduction and the increase in flow rate can be achieved. Therefore, a porous membrane with a small pore size and a large flow rate can be manufactured.
[0106] On the other hand, when a varnish containing only an organic solvent (S1) as the solvent (S) is used, or when a varnish containing an organic solvent (S1) and an organic solvent having a boiling point of 200° C. or higher at atmospheric pressure but not being a nitrogen-containing polar solvent is used, the flow rate is small and the film strength is also low.
[0107] The boiling point of the organic solvent (S1) may be lower than 200°C, but is preferably 180°C or lower, more preferably 170°C or lower. The boiling point of the organic solvent (S1) is preferably 100°C or higher, more preferably 120°C or higher.
[0108] Examples of the organic solvent (S1) include aliphatic amide solvents. Examples of the aliphatic amide solvents as the organic solvent (S1) include dimethylacetamide (boiling point: 165° C.).
[0109] The organic solvent (S1) may be one kind or two or more kinds.
[0110] The boiling point of the organic solvent (S2) may be 200°C or higher, and may be 210°C or higher, or 220°C or higher.
[0111] Examples of the nitrogen-containing polar solvent as the organic solvent (S2) include nitrogen-containing heterocyclic compounds which may have a substituent and aromatic hydrocarbons substituted with a nitrogen-containing group.
[0112] Examples of the nitrogen-containing heterocyclic compound which may have a substituent as the organic solvent (S2) include 1,3-dimethyl-2-imidazolidinone (boiling point: 220° C.), N-methylpyrrolidone (boiling point: 202° C.), and N-ethyl-2-pyrrolidone (boiling point: 218° C.).
[0113] As the nitrogen-containing group, a nitro group can be mentioned.
[0114] As the aromatic hydrocarbon substituted with a nitrogen-containing group as the organic solvent (S2), nitrobenzene (210°C) can be mentioned.
[0115] The organic solvent (S2) may be one kind or two or more kinds.
[0116] It should be noted that, in order to form a porous membrane, the solvent (S), the organic solvent (S1), and the organic solvent (S2) are solvents that can dissolve the resin component (A) composed of polyamic acid, polyimide, polyamideimide precursor, polyamideimide and / or polyether sulfone contained in the varnish without dissolving the fine particles (B).
[0117] The ratio of the mass of the organic solvent (S2) to the mass of the solvent (S) is preferably 5 mass % to 70 mass %, more preferably 10 mass % to 60 mass %, further preferably 20 mass % to 50 mass %.
[0118] The content of the organic solvent (S2) in the varnish is preferably 100 parts by mass to 900 parts by mass, more preferably 200 parts by mass to 800 parts by mass, and even more preferably 300 parts by mass to 700 parts by mass, relative to 100 parts by mass of the resin component (A).
[0119] [Dispersant]
[0120] For the purpose of uniformly dispersing the particles (B) in the varnish, a dispersant can be further added together with the particles (B). By adding a dispersant, the particles (B) can be more evenly mixed in the varnish, and then, in the film obtained by the varnish film forming, the particles (B) can be evenly distributed. As a result, dense openings can be set on the surface of the porous film finally obtained, and the surface and the back side are efficiently connected, and the air permeability of the porous film is improved. In addition, by adding a dispersant, it is easy to improve the dryness of the varnish, in addition, it is easy to improve the peelability of the formed unfired composite film from a substrate, etc.
[0121] The dispersant is not particularly limited, and known dispersants can be used. For example, anionic surfactants such as coconut oil fatty acid salts, sulfonated castor oil salts, lauryl sulfate salts, polyoxyalkylene allyl phenyl ether sulfate salts, alkylbenzene sulfonic acid, alkylbenzene sulfonate, alkyl diphenyl ether disulfonate, alkyl naphthalene sulfonate, dialkyl sulfosuccinate salts, isopropyl phosphate, polyoxyethylene alkyl ether phosphate salts, polyoxyethylene allyl phenyl ether phosphate salts; cationic surfactants such as oleylamine acetate, lauryl pyridinium chloride, cetyl pyridinium chloride, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, didecyl dimethyl ammonium chloride; coconut oil alkyl dimethyl amine oxide, fatty acid amide propyl dimethyl amine oxide, alkyl polyaminoethyl glycine hydrochloride, amido betaine type surfactant, alanine type surfactant, lauryl imino dipropionic acid, etc. can be cited. Amphoteric surfactants; nonionic surfactants of polyoxyalkylene primary alkyl ethers or polyoxyalkylene secondary alkyl ethers such as polyoxyethylene octyl ether, polyoxyethylene decyl ether, polyoxyethylene lauryl ether, polyoxyethylene lauryl amine, polyoxyethylene oleyl amine, polyoxyethylene polystyryl phenyl ether, polyoxyalkylene polystyryl phenyl ether, polyoxyethylene dilaurate, polyoxyethylene laurate, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, sorbitan laurate, polyoxyethylene sorbitan laurate, fatty acid diethanolamide and other polyoxyalkylene nonionic surfactants; fatty acid alkyl esters such as octyl stearate and trimethylolpropane tricaprate; polyether polyols such as polyoxyalkylene butyl ether, polyoxyalkylene oleyl ether, and trimethylolpropane tri(polyoxyalkylene) ether, but not limited to these. In addition, two or more of the above dispersants may be used in combination.
[0122] In the varnish, for example, from the perspective of film-forming properties, the content of the dispersant relative to the mass of the above-mentioned fine particles (B) is preferably 0.01 mass % to 5 mass %, more preferably 0.05 mass % to 1 mass %, and even more preferably 0.1 mass % to 0.5 mass %.
[0123] The method for producing the porous film-producing composition (varnish) is not particularly limited.
[0124] Typically, the varnish is produced by the following steps: a particle dispersion preparation step of dispersing the particles (B) in a solvent; a step of preparing a resin solution containing the resin component (A); and a kneading step of combining the particle dispersion and the resin solution, kneading and adjusting the concentration.
[0125] The varnish preferably has a viscosity of 0.1 to 3 Pa·s at 25° C. and a solid content of 10% to 50% by mass. The varnish can be produced by kneading for preferably 2 minutes to 10 hours, more preferably 2 minutes to 60 minutes.
[0126] In addition, the viscosity of a varnish can be measured using an E-type viscometer.
[0127] For kneading of the varnish, a rotation / revolution mixer (trade name: Takurentaro, manufactured by Thinky Co., Ltd.), a planetary mixer, a bead mill, or the like can be used.
[0128] In addition, in the kneading step, the following can be performed: using a 2 Above 785000μm 2 The dispersion device of the following flow path is used to disperse a mixed solution (slurry) containing a microparticle dispersion and a resin solution pressurized to 50 MPa or more through the flow path. As a method for such a dispersion process through the flow path, the method described in Japanese Patent Publication No. 2020-104105 can be cited.
[0129] 《Method for producing porous membrane》
[0130] The method for manufacturing a porous membrane includes the following steps: a composite membrane forming step, forming a composite membrane formed by the aforementioned porous membrane manufacturing composition on a substrate; a heating step, heating the composite membrane to remove a portion of the solvent (S) from the composite membrane; and a particle removal step, removing the particles (B) from the composite membrane after the heating step.
[0131] In addition, the method for producing a porous membrane may include the resin component (A) containing at least one of a polyamic acid and a polyamideimide precursor, and the method may include a calcining step of calcining the composite membrane during the heating step or after the heating step and before the particle removal step.
[0132] [Composite film forming step (production of unfired composite film)]
[0133] In the composite film forming step, a composite film made of the porous film producing composition (varnish) is formed on a substrate.
[0134] Composite film (hereinafter, also recorded as "unfired composite film".) can be directly formed (film-forming) on a substrate, or formed (film-forming) on a lower film different from the above-mentioned unfired composite film. In addition, it is also possible to further make an upper film different from the above-mentioned unfired composite film in the upper layer after using the aforementioned varnish (porous film manufacturing composition) to make an unfired composite film. It should be noted that in the present application, a method for arranging a lower film on a substrate, and a method for further making an upper film different from the above-mentioned unfired composite film in the upper layer after using the aforementioned varnish to make an unfired composite film are both included in the method for forming an unfired composite film on a substrate. Wherein, when the resin component (A) contained in the aforementioned varnish is a polyamic acid or polyamide-imide precursor and a material that does not require a firing process is used in the upper film, an upper film can also be formed on the resin-particle composite film after firing.
[0135] The composite film (unfired composite film) composed of the varnish described above is preferably formed on a substrate in the form of a single-layer film.
[0136] Examples of the substrate include a PET film, a SUS substrate, and a glass substrate.
[0137] As the above-mentioned lower film (or upper film), for example, can enumerate the lower layer (or upper strata) unfired composite film obtained by using lower layer (or upper strata) film varnish to carry out film forming, the lower layer (or upper strata) film varnish contains the resin composition, particulate and solvent composed of polyamic acid, polyimide, polyamide-imide precursor, polyamide-imide and / or polyether sulfone, and the content of the above-mentioned particulate is greater than 40 volume % and is below 81 volume % relative to the total of the above-mentioned resin composition and the above-mentioned particulate. The lower layer (or upper strata) unfired composite film can also be formed on the substrate. If the content of the above-mentioned particulate is greater than 40 volume %, then particles are uniformly dispersed, in addition, if the content of the above-mentioned particulate is below 81 volume %, then disperse in the mode that particles do not agglomerate each other, therefore can uniformly form holes in porous film. Furthermore, when the content of the fine particles is within the above range, when a lower layer (or upper layer) unfired composite film is formed on a substrate, even if a release layer is not provided on the substrate in advance, it is easy to ensure releasability after film formation.
[0138] It should be noted that the particles used in the lower (or upper) film varnish may be the same as or different from the particles (B) used in the aforementioned varnish. In order to make the pores in the lower (or upper) unfired composite film denser, the particles used in the lower (or upper) film varnish preferably have a smaller or the same particle size distribution index as the particles (B) used in the aforementioned varnish. Alternatively, the particles used in the lower (or upper) film varnish preferably have a smaller or the same sphericity as the particles (B) used in the aforementioned varnish.
[0139] In addition, the average particle size of the microparticles used in the lower layer (or upper layer) film varnish may be the same as or different from the average particle size of the microparticles (B) of the aforementioned varnish. The average particle size may be suitably set in the range of more than 10 nm and less than 5000 nm according to the purpose. When using the lower layer (or upper layer) film varnish, it is preferred to make the aforementioned varnish the upper layer, and use different lower layer film varnishes such as the average particle size of the microparticles or the particle size distribution index in combination.
[0140] In addition, the content of microparticles in the varnish for forming the lower layer (or upper layer) film may be more than the aforementioned varnish, or less than the aforementioned varnish. Preferred examples of components such as resin components, microparticles and solvents contained in the varnish for forming the lower layer (or upper layer) film are the same as those of the aforementioned varnish. The varnish for forming the lower layer (or upper layer) film can be prepared by the same method as the aforementioned varnish. The lower layer unfired composite film can be formed, for example, by the following method: applying the above-mentioned varnish for forming the lower layer film on a substrate, and drying it at 0 to 100° C. (preferably at normal pressure and 10 to 100° C.) under normal pressure or vacuum. The film-forming conditions of the upper layer unfired composite film are also the same.
[0141] In addition, as the above-mentioned lower layer (or upper layer) membrane, for example, there can also be mentioned a lower layer membrane formed by fiber materials such as cellulose resin, non-woven fabric (for example, polyimide non-woven fabric, etc. The fiber diameter is, for example, about 50nm to about 3000nm), and a polyimide membrane.
[0142] Then, the process proceeds to a firing step, that is, the unfired composite film or the laminated film of the unfired composite film and the lower (or upper) film is fired to obtain a polyimide-microparticle composite film. When the unfired composite film or the lower unfired composite film is formed on a substrate, the firing may be performed directly, or the unfired composite film or the laminated film of the unfired composite film and the lower unfired composite film may be peeled off from the substrate before the process proceeds to the firing step.
[0143] It should be noted that, when the above-mentioned lower layer (or upper layer) film in the laminated film is a lower layer (or upper layer) unfired composite film obtained by film formation using a varnish for the lower layer (or upper layer), and the composition of the varnish for the lower layer (or upper layer) film is the same as the composition of the aforementioned varnish, the laminated film of the above-mentioned composite film (unfired composite film) and the above-mentioned lower layer (or upper layer) film is essentially one layer (single layer), but is referred to as a laminated film in this specification.
[0144] When the composite film (unfired composite film) or the laminated film of the unfired composite film and the lower layer (or upper layer) unfired composite film is peeled off from the substrate, in order to further improve the peelability of the film, a substrate pre-set with a release layer can also be used. In the case of pre-setting a release layer on the substrate, before applying varnish, a release agent is applied on the substrate and dried or sintered. Regarding the release agent used herein, known release agents such as alkyl phosphate ammonium salts, fluorine systems or silicon can be used without particular restriction. When the above-mentioned unfired composite film is peeled off from the substrate, a small amount of release agent remains on the peeling surface of the unfired composite film, so it will also cause discoloration during firing and adverse effects on electrical properties, so it is preferably removed as much as possible. For the purpose of removing the release agent, a washing process can be introduced in which an organic solvent is used to wash the unfired composite film or the laminated film of the unfired composite film and the lower layer unfired composite film after peeling off from the substrate.
[0145] On the other hand, when the substrate is directly used without providing a release layer in the film formation of the unfired composite film or the lower layer unfired composite film, the release layer forming step and the washing step can be omitted. In addition, in the manufacture of the unfired composite film, before the firing step described later, an immersion step in a solvent containing water, a pressurization step, and a drying step after the immersion step can also be provided as optional steps.
[0146] [Heating process]
[0147] In the heating step, the composite film (uncalcined composite film) is heated to remove part of the solvent (S) from the composite film. That is, the heating step is a drying step.
[0148] In the heating step, the composite film is heated under the conditions that at least a portion of the organic solvent (S1) can be removed from the composite film and a portion of the organic solvent (S2) remains in the composite film.
[0149] The heating temperature is, for example, preferably 40° C. to 170° C., more preferably 60° C. to 145° C. The heating step may be performed under normal pressure, reduced pressure, or vacuum.
[0150] Since the organic solvent (S2) remains in the composite membrane during heating, the organic solvent (S2) interacts with the resin component (A), and the orientation of the resin component (A) is improved. Therefore, the strength of the composite membrane after the heating process (after the drying process) is improved, and the reduction in the flow rate of the fluid (liquid, gas) passing through the porous membrane due to pore collapse can be suppressed, and the flow rate can be improved (increased).
[0151] [Firing step (production of resin-microparticle composite film)]
[0152] The calcining step is a step of calcining the composite film during the heating step or after the heating step and before the particle removal step.
[0153] The calcining step may be performed after the heating step (drying step) or during the heating step. That is, the heating in the calcining step may also serve as the heating (drying) in the heating step.
[0154] When the resin component (A) contained in the varnish contains a polyamic acid and / or polyamideimide precursor, a composite film (resin-microparticle composite film) containing a resin formed from polyimide and / or polyamideimide and microparticles (B) can be formed by subjecting the composite film (unfired composite film) to a firing step.
[0155] When the resin component (A) includes polyamic acid and polyamide-imide precursor, in the firing process, when polyamic acid is changed to polyimide and polyamide-imide precursor is changed to polyamide-imide, residual stress is generated due to volume shrinkage, so pore collapse occurs, and the flow rate of the porous membrane formed is easily reduced. However, if the above-mentioned varnish is used, the strength of the fired membrane becomes high, so it is possible to suppress such pore collapse and increase the flow rate of the porous membrane.
[0156] In addition, when the resin component (A) contained in the varnish is polyimide, polyamide-imide or polyether sulfone, a calcining step may be included, but the calcining step may be omitted.
[0157] In the composite film forming step, when the unfired composite film is formed on an underlayer film different from the unfired composite film, the underlayer film is fired together with the unfired composite film in the firing step.
[0158] The calcination temperature in the calcination step varies depending on the structure of the composite film and the lower film and the presence or absence of a condensation agent, but is preferably 120° C. to 450° C., and more preferably 150° C. to 420° C. When an organic material is used in the fine particles (B), it is necessary to set the temperature to be lower than its thermal decomposition temperature.
[0159] When the resin component (A) contained in the varnish is a polyamic acid, it is preferable to complete imidization in the calcining step.
[0160] Regarding the firing conditions, for example, the following methods may be used: a method of heating from room temperature to 400°C over 3 hours and then maintaining at 400°C for 20 minutes; a stepwise drying-heat imidization method of heating from room temperature to 400°C in steps of 50°C (maintaining for 20 minutes at each step) and finally maintaining at 400°C for 20 minutes. When an unfired composite film is formed on a substrate and the unfired composite film is temporarily peeled off from the substrate, a method of fixing the end of the unfired composite film to a SUS mold or the like to prevent deformation may be used.
[0161] The film thickness of the completed resin-particle composite film can be obtained, for example, by measuring the thickness of multiple locations using a micrometer or the like and taking the average value. The preferred average film thickness varies depending on the use of the porous film. For example, when used for a separator, it is preferably 5 μm to 500 μm, more preferably 10 μm to 100 μm, and further preferably 15 μm to 30 μm. When used for a filter, it is preferably 5 μm to 500 μm, more preferably 10 μm to 300 μm, and further preferably 20 μm to 150 μm.
[0162] [Microparticle Removal Step (Making the Resin-Microparticle Composite Film Porous)]
[0163] In the particle removal step, the particles (B) are removed from the composite film after the heating step (in the case of a calcination step, the composite film (resin-particle composite film) after the calcination step). By selecting an appropriate method to remove the particles (B), a porous film can be manufactured with good reproducibility.
[0164] For example, when silicon dioxide is used as the material of the fine particles (B), the resin-fine particle composite film can be treated with a low-concentration hydrogen fluoride aqueous solution or the like to dissolve and remove the silicon dioxide.
[0165] As the material of the microparticles (B), organic materials can also be selected. As an organic material, as long as it is an organic material that decomposes at a low temperature compared to the resin contained in the resin-microparticle composite film, it can be used without particular limitation. For example, resin microparticles formed by linear polymers and known depolymerizable polymers can be cited. The molecular chains of conventional linear polymers break randomly during thermal decomposition, and depolymerizable polymers are polymers that decompose into monomers during thermal decomposition. All disappear from the porous membrane by decomposing into low molecular weight bodies or CO2. The decomposition temperature of the resin microparticles used is preferably above 230°C and below 320°C.
[0166] The overall thickness of the porous membrane is not particularly limited. For example, when used for a separator, it is preferably 5 μm to 500 μm, more preferably 10 μm to 100 μm, and further preferably 15 μm to 30 μm. When used for a filter, it is preferably 5 μm to 500 μm, more preferably 10 μm to 300 μm, and further preferably 20 μm to 150 μm. The above-mentioned membrane thickness is the same as that of the resin-particle composite membrane, and can be obtained by measuring the thickness of multiple locations using a micrometer and taking the average value.
[0167] In the case where the porous film is formed by two or more porous film manufacturing compositions, the ratio of the thickness direction of the region formed by each porous film manufacturing composition can be appropriately set according to the purpose of the porous film. In the case of a porous film having two regions of a layer (I) obtained from a porous film manufacturing composition and a layer (II) obtained from another porous film manufacturing composition, the ratio of the thickness direction of each region ((I): (II)) can be prepared in the range of, for example, 1:99 to 99:1, preferably 5:95 to 95:5. The thickness of each layer can be calculated by observing multiple locations of the porous film cross section using a scanning electron microscope (SEM) or the like and taking the average value.
[0168] [Resin removal process]
[0169] The method for producing a porous film may include a resin removal step of removing at least a portion of the resin portion of the resin-microparticle composite film before the microparticle removal step, or removing at least a portion of the porous film after the microparticle removal step. By removing at least a portion of the resin portion of the resin-microparticle composite film or at least a portion of the porous film, the porosity of the porous film of the final product can be increased compared to a case where the resin portion is not removed.
[0170] The above-mentioned step of removing at least a part of the resin portion or the step of removing at least a part of the porous film can be performed by a common chemical etching method or a physical removal method, or a method combining these methods.
[0171] As a chemical etching method, treatment using a chemical etching solution such as an inorganic alkaline solution or an organic alkaline solution can be cited. An inorganic alkaline solution is preferred. As an inorganic alkaline solution, for example, a hydrazine solution containing hydrazine hydrate and ethylenediamine, a solution of an alkali metal hydroxide such as potassium hydroxide, sodium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, an ammonia solution, an etching solution with alkaline hydroxide, hydrazine and 1,3-dimethyl-2-imidazolidinone as main components, etc. can be cited. As an organic alkaline solution, primary amines such as ethylamine and n-propylamine; secondary amines such as diethylamine and di-n-butylamine; tertiary amines such as triethylamine and methyldiethylamine; alcohol amines such as dimethylethanolamine and triethanolamine; quaternary ammonium salts such as tetramethylammonium hydroxide and tetraethylammonium hydroxide; alkaline solutions of cyclic amines such as pyrrole and piperidine can be cited.
[0172] The solvent of each of the above solutions can be appropriately selected from pure water and alcohols. Alternatively, a solution to which an appropriate amount of a surfactant is added can be used. The alkali concentration is, for example, 0.01 to 20% by mass.
[0173] In addition, as a physical method, for example, dry etching using plasma (oxygen, argon, etc.), corona discharge, etc., a surface treatment method by dispersing an abrasive (for example, aluminum oxide (hardness 9)) in a liquid and irradiating it to the film surface at a speed of 30 to 100 m / s, etc. can be used.
[0174] The above method is suitable because it can be applied to any resin removal step before or after the fine particle removal step.
[0175] On the other hand, as a physical method applicable only to the resin removal step performed after the particle removal step, the following method can be adopted: after the target surface is pressed against a backing film (for example, a polyester film such as a PET film) moistened with a liquid, the porous film is peeled off from the backing film without drying or after drying. Due to the surface tension of the liquid or the electrostatic adhesion, the porous film is peeled off from the backing film in a state where only the surface layer of the porous film remains on the backing film.
[0176] According to the method for manufacturing the porous membrane described above, the flow rate of the fluid (liquid, gas) passing through the porous membrane can be improved (increased). Therefore, it is possible to simultaneously achieve a small pore size and an increase in flow rate. Therefore, it is possible to manufacture a porous membrane with a small pore size and a large flow rate.
[0177] In addition, in the porous membrane produced by the above-mentioned method for producing a porous membrane, the organic solvent (S2) (nitrogen-containing polar solvent having a boiling point of 200° C. or higher) remains.
[0178] The IPA flow rate of the produced porous membrane measured by the method described in [IPA flow rate (FR)] described later is, for example, 0.21 mL / (min·cm 2 ) or more, and can also be set to 0.25mL / (min·cm 2 )above.
[0179] The produced porous membrane may have a bubble point measured by the method described in [Bubble Point (BP)] described later, which is, for example, 80 psi or more, or 90 psi or more.
[0180] It should be noted that the bubble point is an indicator of the pore diameter of the interconnected pores, and the higher the bubble point, the smaller the pore diameter.
[0181] The produced porous membrane may have a tensile strength measured by the method described in [Tensile Strength] below, for example, of 28 MPa or more, or 30 MPa or more.
[0182] The porous membrane to be produced includes a structure in which spherical pores are connected to each other (hereinafter referred to as connected pores). The openings in the porous membrane refer to portions where the connected pores open on the surface of the porous membrane.
[0183] The spherical shape in relation to the shape of the hole is a concept including a spherical shape, but is not necessarily limited to a spherical shape. The spherical shape may be substantially a spherical shape, and a shape that can be recognized as a substantially spherical shape when visually checking an enlarged image of the hole portion is also included in the spherical shape.
[0184] Specifically, in the spherical hole, the surface defining the hole portion is a curved surface, and a spherical or substantially spherical hole is defined by the curved surface.
[0185] Typically, each spherical hole is a hole formed by removing each particle (B) present in the composite film (resin-particle composite film) in a subsequent process, i.e., a particle removal process. In addition, the interconnected hole is formed by removing a plurality of particles (B) present in contact with each other in the resin-particle composite film in a subsequent process, i.e., a particle removal process, in a method for manufacturing a porous film. The portion where the spherical holes in the interconnected hole are connected comes from the portion where the plurality of particles (B) were in contact with each other before being removed.
[0186] The diameter of the openings of the porous membrane can be appropriately changed within a range of, for example, 100 nm to 5000 nm depending on the intended use of the porous membrane.
[0187] The diameter of the opening is equal to or substantially equal to the diameter of the spherical pores constituting the communicating pores. The communicating pores formed by connecting spherical pores of such diameters allow fluid to pass well in the porous membrane.
[0188] The porous membrane has internally connected holes penetrating the porous membrane in the thickness direction as flow paths for the fluid, thereby allowing the fluid to pass from one main surface of the porous membrane to the other main surface.
[0189] In addition, when the laminate is used as a filter, the fluid passes through the inside of the porous membrane while contacting the curved surface defining each spherical hole. The contact area of the fluid inside the porous membrane is quite large due to the interconnecting holes formed by the spherical holes. Therefore, it is believed that if the fluid is passed through the laminate including the porous membrane, the microscopic substances present in the fluid are easily adsorbed to the spherical holes in the porous membrane.
[0190] 《Porous membrane》
[0191] The porous membrane contains at least one resin component selected from the group consisting of polyimide, polyamideimide, and polyethersulfone, and an organic solvent (S2) which is a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure.
[0192] The porous membrane is manufactured by a manufacturing method comprising the following steps: forming a composite membrane formed of the above-mentioned porous membrane manufacturing composition (varnish) on a substrate; heating the composite membrane to remove a part of the solvent (S) from the composite membrane; and removing the fine particles (B) from the heated composite membrane. That is, the porous membrane can be manufactured by the above-mentioned porous membrane manufacturing method.
[0193] Since the porous membrane is manufactured using the aforementioned porous membrane manufacturing composition (varnish), the flow rate of the fluid permeating from the porous membrane can be increased. Therefore, it is possible to simultaneously achieve a small pore size and an increase in flow rate. Therefore, it is possible to provide a porous membrane with a small pore size and a large flow rate.
[0194] Example
[0195] Hereinafter, the present invention will be described in more detail with reference to Examples, but the scope of the present invention is not limited to the following Examples.
[0196] [Examples 1-2 and Comparative Examples 1-2]
[0197] A silica dispersion (containing 0.5% by mass of a dispersant relative to silica) was added to the polyamic acid solution in such a manner that the amount of polyamic acid was 30% by mass and the mass of silica was 70% by mass relative to the total mass of the polyamic acid (resin component (A)) and the mass of silica (fine particles (B)). Furthermore, organic solvents (1), (2) and / or organic solvents (S') not belonging to the organic solvents (1) and (2) were added as the solvents (S) in such a manner that the composition of the solvent (S) in the final composition (composition for producing a porous film (varnish)) as a whole became the mass % described in Table 1.
[0198] The obtained mixed solution was stirred at 4000 rpm for 30 minutes in a container with a capacity of 1000 mL to disperse it. Then, a 60 μm diameter (cross-sectional area of 2826 μm) manufactured by Yoshida Machinery Co., Ltd. was used. 2 ) was used to disperse the mixed solution through the flow path at 200 MPa for 10 times, thereby preparing a composition for manufacturing a porous membrane (varnish) having a solid content concentration of 30% by mass. It should be noted that the ratio of polyamic acid to silicon dioxide (polyamic acid: silicon dioxide) in the obtained varnish was 38:62 in volume ratio and 30:70 in mass ratio.
[0199] In addition, the polyamic acid solution, organic solvent, dispersant, and fine particles shown below were used.
[0200] Polyamic acid solution: reaction product of pyromellitic dianhydride and 4,4'-diaminodiphenyl ether (solid content: 20% by mass (organic solvent: N,N-dimethylacetamide))
[0201] Organic solvent (S1): N,N-dimethylacetamide (DMAc)
[0202] Organic solvent (S2): N-methylpyrrolidone (NMP) or 1,3-dimethyl-2-imidazolidinone (DMI)
[0203] Organic solvent (S'): γ-butyrolactone (GBL)
[0204] Dispersant: Polyoxyethylene secondary alkyl ether dispersant
[0205] · Microparticles (B): Silica with an average particle size of 100 nm
[0206] The obtained composition for producing a porous membrane is applied to a polyethylene terephthalate (PET) film as a substrate using an applicator, thereby forming a composite membrane on the substrate (composite membrane forming process). Next, the composite membrane (unfired composite membrane) is heated at 90°C for 5 minutes to remove a portion of the solvent (S) (heating process). The composite membrane after the heating process is placed in an oven and fired at 380°C for 15 minutes to complete imidization to obtain a resin-particle composite membrane (firing process). Then, the resin-particle composite membrane is peeled off from the substrate. The peeled resin-particle composite membrane is immersed in hydrogen fluoride (HF) for 10 minutes to remove the silica particles contained in the membrane (particle removal process). Then, it is washed with water and dried to obtain polyimide porous membranes of Examples 1 to 2 and Comparative Examples 1 to 2, each with a film thickness of 40 μm. It should be noted that in the polyimide porous membranes of Examples 1 and 2, an organic solvent (S2) remains.
[0207] The IPA flow rate (FR), bubble point (BP), and tensile strength of the obtained porous polyimide membranes of Examples and Comparative Examples were measured by the following methods.
[0208] [IPA flow rate (FR)]
[0209] Each polyimide porous membrane was cut into a membrane filter size of 47 mm in diameter and mounted on an in-line filter holder. Next, isopropyl alcohol (IPA) was filtered by pressurizing it with 0.1 MPa air from the upstream side (upstream side of the flow path of the porous membrane), and its flow rate was measured. The measurement was carried out at 25°C. In Table 1, the flow rate per 1 cm 2 , expressed in mL per minute.
[0210] [Bubble Point (BP)]
[0211] The bubble point (BP) was measured in accordance with ASTM F316-86 and JIS K 3832. Specifically, each polyimide porous membrane was cut into a membrane filter size of 47 mm in diameter and mounted on a bubble point measurement bracket. The downstream side of the membrane (the downstream side of the flow path of the porous membrane) was moistened with a fluorine-based solvent (Novec 7200, manufactured by 3M, hydrofluoroether), and the pressure at which bubbles were generated on the downstream side was measured by slowly pressurizing with air from the upstream side. The measurement was performed at room temperature (25°C).
[0212] [Tensile strength]
[0213] Each polyimide porous film was cut into a dumbbell No. 6 shape to prepare a test piece. A small tabletop tester EZ Test EZ-SX (manufactured by Shimadzu Corporation) was used as a tester, and the stress (tensile strength (MPa)) at break of the test piece was measured under the measurement conditions of 25°C and 5 mm / min in accordance with JIS K 7127.
[0214] [Table 1]
[0215]
[0216] As shown in Table 1, the flow rate of Examples 1 to 2 using a composition for producing a porous membrane containing an organic solvent having a boiling point of less than 200°C at atmospheric pressure (organic solvent (S1)) and a nitrogen-containing polar solvent having a boiling point of 200°C or more at atmospheric pressure (organic solvent (S2)) as a solvent (S) is 10% or more higher than that of Comparative Example 1 using a composition for producing a porous membrane containing only an organic solvent (S1) and Comparative Example 2 using a composition for producing a porous membrane containing only an organic solvent (S1) and an organic solvent having a boiling point of 200°C or more but not a nitrogen-containing polar solvent. In particular, the flow rate of Example 1 is higher than that of Example 2. In addition, the bubbling points of Examples 1 to 2 and Comparative Examples 1 to 2 are of the same degree (100 psi), and it can be said that the pore diameters are all small. Therefore, Examples 1 to 2 obtain porous membranes that simultaneously achieve a small pore diameter and an increase in flow rate. In addition, the membrane strength of Examples 1 to 2 is also higher than that of Comparative Examples 1 to 2. In particular, the membrane strength of Example 1 is higher than that of Example 2.
Claims
1. A composition for producing a porous membrane, comprising a resin component (A), fine particles (B) and a solvent (S), wherein the resin component (A) is at least one selected from the group consisting of polyamic acid, polyimide, a polyamideimide precursor, polyamideimide and polyethersulfone, The solvent (S) comprises an organic solvent (S1) and an organic solvent (S2), The organic solvent (S1) is an organic solvent having a boiling point below 200° C. under atmospheric pressure, The organic solvent (S2) is a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure.
2. The composition for producing a porous film according to claim 1, wherein The nitrogen-containing polar solvent as the organic solvent (S2) is at least one selected from the group consisting of nitrogen-containing heterocyclic compounds which may have a substituent and aromatic hydrocarbons substituted with a nitrogen-containing group.
3. The composition for producing a porous film according to claim 2, wherein The organic solvent (S2) is at least one selected from the group consisting of 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, N-ethyl-2-pyrrolidone, and nitrobenzene.
4. The composition for producing a porous film according to claim 1, wherein The organic solvent (S1) is an aliphatic amide solvent.
5. The composition for producing a porous film according to claim 4, wherein The organic solvent (S1) is dimethylacetamide.
6. The composition for producing a porous film according to claim 1, wherein The ratio of the mass of the organic solvent (S2) to the mass of the solvent (S) is 5 mass % or more and 70 mass % or less.
7. The composition for producing a porous film according to claim 1, wherein The content of the organic solvent (S2) is 100 parts by mass or more and 900 parts by mass or less relative to 100 parts by mass of the resin component (A).
8. A method for producing a porous membrane, comprising the following steps: a composite film forming step of forming a composite film formed from the porous film producing composition according to any one of claims 1 to 7 on a substrate; a heating step of heating the composite film to remove a portion of the solvent (S) from the composite film; and The fine particle removal step is to remove the fine particles (B) from the composite film after the heating step.
9. The method for producing a porous membrane according to claim 8, wherein: The resin component (A) comprises at least one of a polyamic acid and a polyamide-imide precursor, The manufacturing method includes a firing step of firing the composite film during the heating step or after the heating step and before the particle removal step.
10. A porous membrane comprising at least one resin component selected from the group consisting of polyimide, polyamideimide and polyethersulfone, and a nitrogen-containing polar solvent having a boiling point of 200° C. or higher under atmospheric pressure, The porous membrane is manufactured using a manufacturing method comprising the following steps: a step of forming a composite membrane formed from a porous membrane manufacturing composition described in any one of claims 1 to 7 on a substrate; a step of heating the composite membrane to thereby remove a portion of the solvent (S) from the composite membrane; and a step of removing the particles (B) from the heated composite membrane.
Citation Information
Patent Citations
Transfer paper conveying device
JP1981005566A
Selective semipermeable membrane of polyamideimide
JP1988283705A
Polyamide-imide preferential segregation membrane
JP1990198619A
Porous film manufacturing method, method for manufacturing composition for manufacture of porous film, and porous film
JP2020104105A
Cited By
Method for preparing polyimide gas separation membrane through in-situ fluorination
CN121490605A